2017
DOI: 10.5296/jas.v5i4.12170
|View full text |Cite
|
Sign up to set email alerts
|

Response of Jatropha integerrima Plants Irrigated with Different Levels of Saline Water to Nano Silicon and Gypsum

Abstract: An open field experiment was carried out during 2015 and 2016 seasons at the experimental nursery of the Ornamental Horticulture Department, Faculty of Agriculture, Cairo University, Egypt. The purpose of present research was to investigate the effect of foliar application of nano silicon with different concentrations and gypsum soil application on growth, flowering and chemical constituents of Jatropha integerrima plants irrigated with different levels of saline water. The concentrations of saline water were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
2
0
0
Order By: Relevance
“…In addition, reports have shown that Si treatment results in short-term accumulation of phenolics followed by a subsequent decline, signalling Si formulation-induced mitigation of salt stress effect, and hence stress alleviation [75,103]. In line with our findings, studies have also reported a Si-mitigated decline in the content of phenolics in salt-stressed apples and Jatropha integerrima, respectively [104,105]. In conclusion, application of Si-based formulations on salt-stressed plants confers higher tolerance thereof via accumulation of phenolics which, in turn, activate defence-related proteins, repair and regulate photosynthetic apparatus, scavenge ROS, inhibit ROS-producing enzymes as well as activate antioxidant enzymes.…”
Section: Si-based Biostimulant Altered Secondary Metabolism Towards the Salt-stress Alleviation In Tomato Plantssupporting
confidence: 90%
“…In addition, reports have shown that Si treatment results in short-term accumulation of phenolics followed by a subsequent decline, signalling Si formulation-induced mitigation of salt stress effect, and hence stress alleviation [75,103]. In line with our findings, studies have also reported a Si-mitigated decline in the content of phenolics in salt-stressed apples and Jatropha integerrima, respectively [104,105]. In conclusion, application of Si-based formulations on salt-stressed plants confers higher tolerance thereof via accumulation of phenolics which, in turn, activate defence-related proteins, repair and regulate photosynthetic apparatus, scavenge ROS, inhibit ROS-producing enzymes as well as activate antioxidant enzymes.…”
Section: Si-based Biostimulant Altered Secondary Metabolism Towards the Salt-stress Alleviation In Tomato Plantssupporting
confidence: 90%
“…On the opposite, higher significant values of Na and Cl % resulted from the control plants in the two seasons. These results agree with those of Ashour (2017) who reported that SiO2NPs foliar application (1 and 2 mM) had positive effects on chemical constituents, at the same time reducing the accumulation of Na + and Cl -% in Jatropha integerrima. Also, Salachna et al (2019) found that 100 ppm AgNPs gave the highest values of chl.…”
Section: Resultssupporting
confidence: 93%